Beyond active learning: a case study of teaching practices in an occupation-centered curriculum. - Hooper B (American Journal of Occupational Therapy)
Although occupation-centered curricula are highly promoted, the teaching processes that convey such designs remain unclear. This case study elucidated occupation-centered teaching practices. Interview and observational data were collected over 8 weeks, and analysis involved coding transcriptions, data matrices, concept maps, journaling, and writing. Participants augmented active learning strategies with strategies that linked course topics to the subject of occupation. The use of linking strategies suggested that: (a) course content was treated as two-tiered; (b) neither content nor instructional processes were inherently occupation-centered; and (c) subject-centered education strengthens social learning theories. Although curricula may appear occupation-centered based on a curriculum description and course content, ultimately 'linking opportunities' in the classroom constitute an essential feature that demarcates a program as occupation-centered.